PENGARUH HARGA, PROMOSI DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN JASA OJEK ONLINE (MAXIM KOTA BENGKULU) - Bayu Putra Ananda; Syofian Syofian; Markoni Markoni (Bisnis-Net, 2023)
This study was  determine the effect price promotion and service quality customer satisfaction  online motorcycle taxi services. populationthis study people the cityBengkulu who Maxim application. The number samples obtained 120 respondents using  16 formula. data analysis method used  multiple linear regression. The results study show that (1) Price  no significant effect on Online Motorcycle taxi services Maxim Bengkulu City, (2) Promotion has significant effect on Online Motorcycle taxi services Maxim Bengkulu City, (3) Quality  not significantly affect Online Motorcycle taxi services Maxim Bengkulu City, (4) Customer satisfaction  no significant effect on online taxi services Maxim Bengkulu City.